In Situ Synthesis of 3D Pt/CdS/ Hydrogenated BiOBr Microspheres with Enhanced Visible Light Photocatalytic Activity. Issue 17 (1st May 2019) - Ye, Jin; Fu, Congcong; He, Jiahui; Zhou, Xuejian; Sun, Yangyang; Liu, Jiahui; Zhang, Yue; Xu, Lidong; Wang, Juan; Yang, Yongfang
Abstract: The construction of heterojunction, the loading of noble metals and introduction of oxygen vacancies are an effective technology to enhance catalyst photocatalytic activity using solar energy. In this paper, 3D Pt/CdS/h‐BiOBr microspheres were successfully synthesized by the method of solvothermal and multiple depositions. Photocatalytic activity of all samples was investigated by degrading methylene blue (MB) under visible light. Among the catalysts, 3D Pt/CdS/h‐BiOBr sample has excellent photocatalytic activity due to improving its light harvesting and charge separation by establishment of heterostructure, which is 1.17, 1.67 and 3.39 times of h‐BiOBr/CdS, h‐BiOBr and BiOBr, respectively Abstract : Herein, 3D Pt/CdS/h‐BiOBr microspheres were successfully synthesized by the method of solvothermal and multiple depositions. 3D Pt/CdS/h‐BiOBr microspheres possessed the highest photocatalytic efficiency towards MB degradation due to synergistic effect of oxygen vacancy, the formation of heterostructure and SPR effect.